Effect of Using Enzyme Complex on Productivity and Hatchability of Broiler Breeders Fed a Corn-Soybean Meal Diet - Malekian Gh; Zamani Moghaddam AK; Khajali F (Poultry Science Journal, 2013)
A total number of  5520 female and  480 male breeders (Arbor Acres plus) at 42wks of age  were used in a 10-week-trial to investigate the effect of an enzyme complex on  the quality  and quantity of egg production as well as hatchability of broiler breeders fed a corn-soybean meal diet. There were two dietary treatment groups: a control group fed on a corn-soybean based diet, and the multi-enzyme group that received the same diet plus an enzyme complex including xylanase, amylase, protease, phytase, ß-glucanase, hemicellulase, and pectinase. Results showed that egg production rate and egg mass were numerically increased as a result of enzyme supplementation and differences between the treatment groups were significant at week 46 (P